The long-term outcomes of CIS patients in the Barcelona inception cohort: Looking back to recognize aggressive MS. (November 2020) - Tintore, Mar; Arrambide, Georgina; Otero-Romero, Susana; Carbonell-Mirabent, Pere; Río, Jordi; Tur, Carmen; Comabella, Manuel; Nos, Carlos; Arévalo, María Jesús; Anglada, Elisenda; Menendez, Rebeca; Midaglia, Luciana; et al.
Objective: To explore the long-term outcomes of patients with clinically isolated syndromes from the Barcelona cohort. Methods: We selected patients with a follow-up longer than 10 years to (1) estimate the risks of multiple sclerosis (MS) and disability accumulation according to the baseline number of T2 lesions and to compare treated versus untreated patients and early versus delayed treatment, and (2) to study baseline features of patients with aggressive MS (Expanded Disability Status Scale (EDSS) ⩾6.0 at 10 years). Results: In all, 401 patients were included (mean follow-up of 14.4 (standard deviation of 2.9) years). A higher number of T2 lesions was associated with an earlier MS diagnosis and an earlier risk of irreversible disability. Early treatment was associated with a decreased risk of EDSS of 3.0: adjusted hazard ratio = 0.4, 95% confidence interval = (0.2, 0.7). Patients with aggressive MS differed in their baseline brain magnetic resonance images: The median (interquartile range) number of T2 lesions and contrast-enhancing lesions (CEL) was 71 (28–95) versus 7 (1–19) and 3 (1–24) versus 0 (0–1), respectively. The cut-offs that better classified patients with aggressive MS were 20 for T2 lesions and 2 for CEL. Conclusion: Although MS natural history is changing, a high lesion load at onset is helpful to identify patients at risk of presenting an aggressive MS.